Analisis Kinerja Sub DAS Bila dengan Pendekatan lahan dan Tata Air - Khairul Anami, Muhammad Fitrah; Lias, Syamsul Arifin; Ahmad, Asmita (Jurnal Ecosolum, 2020)
The watershed can be seen as a natural system where hydrological biophysic processes and community socio-economic activities take place which results in changes in the carrying capacity of watersheds. The issuance of Government Regulation Number 37 of 2012 concerning Watershed Management became the legal basis for the watershed management to evaluate the Performance of Watershed. At present, the watershed hydrology condition in Wajo district is decreasing which causes an increase in sedimentation in Lake Tempe. This study uses the Purposive Sampling method, gravimetry for determining total suspended solid values, and river discharge measurement. The results showed that the value of Total suspended Solid was still relatively good in the range of 0-100 mg L. For land parameters, the percentage of critical land is included in the medium category, the percentage of vegetation cover is in the bad category, and the erosion index is in the very low category. For the parameters of quality, quantity and water continuity, the flow regime coefficient is in the medium category, the annual flow regime coefficient is in the low category, sediment load is in the very low category, and the water use index is in the very good class. So that the performance of Bila Sub-watershed was included in the medium category. The results showed that the performance of Sub-watershed included in the medium category. The performance of Bila Sub-watershed included in the medium category and did not have a significant sedimentation influence to Lake of Tempe, especially in July.